Poly(acrylic acid)-capped and dye-loaded graphene oxide-mesoporous silica : a nano-sandwich for two-photon and photoacoustic dual-mode imaging - Nguyen, Kim Truc (2014)
Growth of mesoporous silica on both sides of graphene oxide affords a nano-sandwich (NS) material. A two-photon active dye is then loaded into the mesopores of the NS followed by sealing with poly(acrylic acid). The obtained hybrid exhibits low cytotoxicity and excellent capability for two-photon and photoacoustic dual-mode bioimaging.